I never knew anyone who peed on themselves on purpose: Exploring adolescent and adult women's lay language and discourse about bladder health and function. Issue 1 (2nd October 2019) - Williams, Beverly Rosa; Nodora, Jesse; Newman, Diane K.; Kane Low, Lisa; James, Aimee S.; Camenga, Deepa R.; Hebert‐Beirne, Jeni; Brady, Sonya S.; Hardacker, Cecilia T.; Smith, Ariana L.; Cunningham, Shayna D.; Burgio, Kathryn L.; et al.
Abstract: Aims: This analysis explored and characterized adolescent and adult women's lay language and discourse related to bladder health/function. Methods: Forty‐four focus groups were conducted across seven United States research centers with 360 adolescents and adult women, organized by six age categories. Multilevel content analyses classified emergent themes. A transdisciplinary lens and inductive approach guided data interpretation. Interpretive insights were validated by a community engagement panel. Results: A repertoire of bladder function terms emerged, including explicit functional terms, formal and polite euphemistic terms, and informal familiar terms, as well as cultural and regional metaphors and idioms. Terminology usage was historically grounded, developmental, and cumulative across the life course. Lay discourse was contextual and affectively valent, suggesting unspoken, commonly understood, situation‐based "rules" for talking about bladder function. Discourse appeared to be siloed within family and friendship circles. Adolescents and adult women often described, rather than named, bladder sensations or problems. Terminology for bladder issues tended to minimize severity and frequency, with medical language only relevant to extreme examples and not applicable to mild episodes. Conclusions: A definitional discordance between medical and lay views of bladder problems was identified, signifying a need to clarify the meaning of medical terms for lay persons. Adolescents and adult women do not have or use standardized precise terminology for bladder health and function, relying instead on social convention and interpersonal context. Findings can be used to foster shared understandings between lay persons and health professionals, informing development of clinical, research, and public health initiatives to promote bladder health.